A measure of cooperativity in non-Arrhenius structural relaxation in terms of the bond strength–coordination number fluctuation model. (January 2017) - Ikeda, Masahiro; Aniya, Masaru
Graphical abstract: Highlights: A measure of cooperativity is employed to study the α-relaxation in a wide temperature range. The cooperativity for fragile polymers melts extends from some dozens to about 100 near T g . The extracted temperature T x from the cooperativity measure enables the characterization of the high-temperature relaxation. Abstract: In order to understand the non-Arrhenius structural relaxation in a systematic way, a measure of cooperativity is employed, which is based on the bond strength–coordination number fluctuation model developed by the authors. In our model, the cooperativity is described by the temperature-dependent number of structural units N B involved in the structural relaxation, which increases from unity at the high temperature limit up to of the order of 100 near the glass transition temperature T g . This is comparable to that estimated by the Donth formula, but is much larger than that obtained from the Adam–Gibbs model. At higher temperature region a characteristic temperature T x is extracted from the cooperativity analysis, which could be associated with the transition temperature T A across which the relaxation behavior changes from Arrhenius-like to non-Arrhenius-like. In the polymer melts and molecular liquids investigated, the characteristic temperature ratio T x / T g is found to be 1.67–1.81, which agrees with the typical T A / T g values reported. The extracted temperature T x enables the characterization of the high-temperature relaxation behavior in a new way that differs from other methods. A possible interpretation of T A is given in terms of the cooperativity onset.